# |
ODE |
Mathematica |
Maple |
\[
{}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right ) x y^{\prime \prime }-2 \left (2 x^{2}-1\right ) y^{\prime }-4 \left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (4 x +1\right ) y^{\prime }+\left (4 x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x -1\right ) y^{\prime \prime }-\left (3 x +2\right ) y^{\prime }-\left (6 x -8\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\alpha t y^{\prime }+\beta y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {2 \left (t +1\right ) y^{\prime }}{t^{2}+2 t -1}+\frac {2 y}{t^{2}+2 t -1} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 t y^{\prime }+\left (4 t^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 t +1\right ) y^{\prime \prime }-4 \left (t +1\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-5 t y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t -1\right )^{2} y^{\prime \prime }-2 \left (t -1\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t -2\right )^{2} y^{\prime \prime }+5 \left (t -2\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\alpha t y^{\prime }+\beta y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+5 t y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {2 \left (t +1\right ) y^{\prime }}{t^{2}+2 t -1}+\frac {2 y}{t^{2}+2 t -1} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 t y^{\prime }+\left (4 t^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 t +1\right ) y^{\prime \prime }-4 \left (t +1\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }-\left (1+3 t \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t -1\right )^{2} y^{\prime \prime }-2 \left (t -1\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t -2\right )^{2} y^{\prime \prime }+5 \left (t -2\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+3 t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-16 x y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x \left (1+y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-{\mathrm e}^{x}\right ) y^{\prime \prime } = {\mathrm e}^{x} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x -2\right ) y^{\prime \prime }+3 y^{\prime }+\frac {4 y}{x^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}+4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x \left (1+y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }-\frac {a^{2} u}{x^{{2}/{3}}} = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }-\frac {2 u^{\prime }}{x}-a^{2} u = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {2 u^{\prime }}{x}-a^{2} u = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {2 u^{\prime }}{x}+a^{2} u = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {4 u^{\prime }}{x}-a^{2} u = 0
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {4 u^{\prime }}{x}+a^{2} u = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-a^{2} y = \frac {6 y}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+n^{2} y = \frac {6 y}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-\left (x^{2}+\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (-9 a^{2}+4 x^{2}\right ) y}{4 a^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {25}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+q y^{\prime } = \frac {2 y}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y \,{\mathrm e}^{2 x} = n^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y}{4 x} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|